Connecting. Drawing for Weaving Relationships (diségno, 2022)
The days of the 42nd International Conference of Teachers of the Disciplines of Representation held in Reggio Calabria from the 16th to the 18th of September 2021, marked the return of the association’s in-presence activities. It is not with a ‘notarial’ emphasis that we speak of them, but rather in recalling their special character: they were the first, in fact, after the pandemic hiatus, which allowed us to rediscover an opportunity to exchange ideas, to elaborate projects for the future, but also to allow individual and collective narratives that were interwoven with the intense days planned in the work program, packed with events and scientific communications. [read more]